A comparison of the frequency of major affective disorder in Huntington's disease and Alzheimer's disease. Issue 11 (November 1985) - Mindham, R H; Steele, C; Folstein, M F; Lucas, J
Abstract : Matched groups of patients suffering from Huntington's disease and Alzheimer's disease were compared for psychiatric morbidity prior to the onset of dementia. The Huntington's disease group showed twice the incidence of major affective disorder. This finding suggests a specific relationship between Huntington's disease and major affective disorder rather than the latter being a non-specific prodromal feature of dementia.